2011
DOI: 10.2174/138161211798357908
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cardiac Mast Cells: Pharmacological Modulation of the Local Renin-Angiotensin System

Abstract: Enhanced production of angiotensin II and excessive release of norepinephrine in the ischemic heart are major causes of arrhythmias and sudden cardiac death. Mast cell-dependent mechanisms are pivotal in the local formation of angiotensin II and modulation of norepinephrine release in cardiac pathophysiology. Cardiac mast cells increase in number in myocardial ischemia and are located in close proximity to sympathetic neurons expressing angiotensin AT1- and histamine H3-receptors. Once activated, cardiac mast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 102 publications
2
41
0
Order By: Relevance
“…Mast cells and histamine release have been implicated in the development of HF [18,20,41]. Our recent research found that H2R activation worsened mitochondrial dysfunction in ischaemic cardiomyocytes and could therefore enhance myocardial apoptosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells and histamine release have been implicated in the development of HF [18,20,41]. Our recent research found that H2R activation worsened mitochondrial dysfunction in ischaemic cardiomyocytes and could therefore enhance myocardial apoptosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…This NE release is reinforced by renin release from mast cells and activation of a local renin-angiotensin cascade [33]. We evaluated possible effects of 4CPI on arrhythmias and release of NE, renin and ␤-hexo in mouse hearts subjected to I/R.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the observed antiproliferative effects of ARBs are basically a reflection of AT1-mediated signaling in cancer cells. This approach does not take into account the possible role of locally produced AngII, which has been demonstrated to be of major importance in other cell types (Reid et al, 2011;Angeli et al, 2013;Lu et al, 2013). In addition, this approach also ignores the possibility of ARBinduced AngII-independent effects which have been demonstrated in other cell types (Alhusban et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration in investigating the effects of ARBs is the concomitant treatment with exogenous AngII (Uemura et al, 2003;Kosaka et al, 2007;Chen et al, 2013), which only blunted AngII-mediated effects. This paradigm ignores AngII-independent effects of candesartan as well as the role of locally produced AngII, which has been well characterized in a variety of tissues and cell types (Reid et al, 2011;Angeli et al, 2013;Lu et al, 2013). Recently, candesartan was shown to be proangiogenic in cerebral microvascular endothelial cells via activation of the angiotensin II type 2 (AT2) receptor (Alhusban et al, 2013).…”
Section: Introductionmentioning
confidence: 99%